8x-3=3x-4

Simple and best practice solution for 8x-3=3x-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x-3=3x-4 equation:


Simplifying
8x + -3 = 3x + -4
Reorder the terms:
-3 + 8x = 3x + -4
Reorder the terms:
-3 + 8x = -4 + 3x
Solving
-3 + 8x = -4 + 3x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-3x' to each side of the equation.
-3 + 8x + -3x = -4 + 3x + -3x
Combine like terms: 8x + -3x = 5x
-3 + 5x = -4 + 3x + -3x
Combine like terms: 3x + -3x = 0
-3 + 5x = -4 + 0
-3 + 5x = -4
Add '3' to each side of the equation.
-3 + 3 + 5x = -4 + 3
Combine like terms: -3 + 3 = 0
0 + 5x = -4 + 3
5x = -4 + 3
Combine like terms: -4 + 3 = -1
5x = -1
Divide each side by '5'.
x = -0.2
Simplifying
x = -0.2

You can always share this solution

See similar equations:

| 8+9q=12+8q | | y-2-2=5 | | -14=-3n+n | | 5(x-2)-6x=-3 | | 5x*-6x=8 | | 3.3=6.5-0.4x | | an=a+(n-1)-0.5 | | 3u+11=62 | | 6x+5=4x-y | | 7-2(6x+3)=10 | | 5n+3o=579 | | -3x-2(x+3)=-1(x+4)-2 | | -32-8x=2x+6(1-8x) | | 2x/5+2=10 | | -3=2b-5b | | 4n-5=2n+9 | | -10y+18=-15y-21+5 | | Y=x^2-3x-11 | | 2x/5=10-2 | | p(4+3)=14+14 | | 16+20x-50=250 | | 6x+18forx=0 | | 2x+4y=(-22) | | 4(-2)=6 | | ab+c(x+1)=d | | 13x-(9x-6)=10 | | -n+2=-5n-6 | | 2x/5+2=10-2 | | -4+7=35y-6 | | 6.2=7.6-0.7x | | 19-3(x+4)+5x=1 | | 5-2x+6x=15-x | | 24+2x=-5(1+6x)-3 | | 8(u+1)=2u+38 | | x(x+3)(x-2)=30 | | 4x+1/9= | | 5t^2+16t+11=0 | | -13x-40=-18x+10 | | 16=2(pi)8 | | b-7+4b=15 | | 7x-6=x | | 5x+6-4=15 | | (x-10)+(3x+6)+(x-11)=180 | | -x^2+10x+35=0 | | 125m-75m+42750=45675-175m | | 4y-7=1 | | 7v-34=-2(v-1) | | (5+2i)-(-4-i)= | | 2x(x+8)+x=180 | | 3x+6x-7=38 | | 2x+7-8x=19-3x | | 29+2x=-5(1+6x)-3 | | 5.6=c/6 | | 5t-t-5=3t-3 | | 12+5m=36 | | -5n-(1+7n)=-8 | | -2y*-8y= | | 18+n=44-n | | -16b=0 | | 4x-6x+2=3+2x | | 6y+1-2y=3+3y+6 | | 5(y-2)=-2(13-9y)+y | | 9y-27=6(y-3) | | -28=-16+m | | 9(x-3)=-3x(2x+4) |


Related pages


derivative of ln tanx5kg in poundsequation simplifier with stepsgcf of 63 and 42expand 2x 3y 3multiplication of fraction calculatorgreatest common factor of 36 and 54solve the absolute value equation calculator2cosx 1 08y xprime factorization of 9273-59factor 2x 2-13x-7cos of 2pitiger algebra comfactor 5x-15y x cosxderivative sinx cosxgraph y 3sinxwhat is the prime factorization of 132decimal inches to fraction calculatorgraph 4x-2ypercent to reduced fraction calculator73-44prime factors of 4406yisqrt x 1dxdtv lwh calculator0.052 conversion factorsinx sin2x sin3xprime factorization of 80cos 3.14what is the prime factorization of 684deriving ln4x 5y 87ax5r 5sgcf of 144equation expression calculator23456789015x5 solvehow to multiply fractions with a calculator11.25 as a fractionconvert 0.65 to a fractionpercent solution calculatorsolve 3x-2y 2what is the gcf of 63greatest common factor of 650.625 as a fraction in simplest form40 prime factorizationcalculator lcmcos pi over 2prime factorization of 85144-64prime factorization of 365what is a prime factorization of 48xln x250000 pounds in dollars2x2 9x 4math homework solver with steps2x y 7 solve for yderivative of e 2t8izderivative of ln 1 xis 3x 5y a linear equation724.5derivative of cos squared xgreatest common factor polynomials calculatorwhats gcfis318